Truth's Fool : Derek Freeman and His War with Anthropology - Hempenstall, Peter J. (Book collections on Project MUSE., 2017)
In 1983 New Zealand anthropologist Derek Freeman ignited a ferocious controversy when he denounced the research of Margaret Mead, a world-famous public intellectual who had died five years earlier. Freeman's claims caught the attention of popular media, converging with other vigorous cultural debates of the era. Many anthropologists, however, saw Freeman's strident refutation of Mead's best-selling Coming of Age in Samoa as the culmination of a forty-year vendetta. Others defended Freeman's critique, if not always his tone. Truth's Fool documents an intellectual journey that was much larger and more encompassing than one might imagine if focusing solely on Freeman's criticism of Mead's work. It peels back the prickly layers to reveal the man in all his complexity. Framing this story within anthropology's development in Britain and America, Peter Hempenstall recounts Freeman's mission to turn the discipline from its cultural-determinist leanings toward a view of human culture underpinned by biological and behavioral drivers. Truth's Fool engages the intellectual questions at the center of the Mead-Freeman debate and illuminates the dark spaces of personal, professional, and even national rivalries. -- from back cover.